CLINICAL CHARACTERISTICS OF VITRECTOMY PATIENTS IN THE CASE OF RHEGMATOGEN RETINA DETACHMENT IN PROF DR R D KANDOU CENTRAL GENERAL HOSPITAL, MANADO - ade John Nursalim; Vera Sumual; Eugeni Jumilia Rachel Sumanti; irene Rumampuk; Christian Maramis Komaling; Stevanus J Loho (International Journal of Retina, 2022)
Abstract Introduction Rhegmatogenous retinal detachmet (RRD) is an ophthalmology urgency that can cause blindness if treated late. Incidence of RRD has increasing overtime. We describe the clinical characteristics of vitrectomy patients in RRD cases at prof dr R D Kandou hospital, north Sulawesi Province, Manado City, Indonesia. Method The study was conducted based on a retrospective search on the medical record data of 72 RRD patients who underwent vitrectomy in the period June 2018-2020. result The most gender was male as many as 43 patients (59.70%), the most age were in the 51-60 years range as many as 33 patients (45.83%), the eyes affected by RRD were mostly right eyes as many as 41 patients (56, 9%), the location of the break was mostly in the superotemporal area as many as 28 (38.9%), the status of the macula was mostly macular off as many as 44 patients (61.10%), the anesthesia used was local anesthesia in 69 patients (95.80 %), the time taken for the procedure was more than 1 month for all patients. conclusion The clinical characteristics of RRD patients at Prof dr R D Kandou Hospital are in line with trends in several places in the world. Time to do vitrectomy need to be evaluated and corrected to improve visual prognosis.